An Economic Analysis of Hydrogen Production Using Wind Power - Yumurtaci, Zehra; Toprak, Kutlay (INT JOURNAL RENEWABLE ENERGY RESEARCH, 2011)
In this study, an economic analysis of wind - hydrogen systems has been carried out. The annual energy output of a private sector wind power facility in Izmir Cesme is used as referenced. According to the annual electrical energy curves of the plant, potential hydrogen amount and electrical energy values are calculated. The hydrogen power plant has been calculated to operate at approximately 30% load factor and the hydrogen cost is found to be 0,033 $/MJ. According to the change of the load factor, the potential electricity costs are calculated and presented in diagrams. Unit hydrogen cost at a load factor of 0,20 is 0,048 $/MJ and falls to 0,015 $/MJ at a load factor of 0,80. The effects increasing power and increasing load factor on the hydrogen unit cost are explained through diagrams and the results are discussed.
Keywords: Wind energy; Hydrogen energy; Economic analysis; Energy & Fuels